Multifunctional Micro/Nanofiber Based‐Dressing Patch with Healing, Protection, and Monitoring Capabilities for Advanced Wound Care. Issue 7 (3rd February 2023) - Ha, Ji‐Hwan; Kim, Jae Yun; Kim, Dahong; Ahn, Junseong; Jeong, Yongrok; Ko, Jiwoo; Hwang, Soonhyoung; Jeon, Sohee; Jung, Young; Gu, Jimin; Han, Hyeonseok; Choi, Jungrak; et al.
Abstract: Considerable efforts have been devoted to developing wound dressings with various functions, including rapid cell proliferation, protection against infection, and wound state monitoring to minimize severe pain and the risks of wound‐caused secondary infections. However, it remains challenging to diagnose wound conditions and achieve integration of the above functions without specialized equipment and expertise in wound care. This study describes an electrospun composite micro/nanofiber‐based bilayer‐dressing patch comprising a healing‐support layer (hyaluronic acid, gelatin, and dexpanthenol) and a protective/monitoring layer (curcumin and polycaprolactone). The improved cell regeneration function and biocompatibility of the healing‐support layer enable rapid healing, as evidenced by the expedited growth of fibroblasts. The superior antimicrobial properties (against Escherichia coli and Staphylococcus aureus ) and visible color changes within the pH range of wound lesions (pH 6–9) of the protective/monitoring layer make the dressing suitable for advanced wound care. The wounds inflicted on BALB/c mice heal rapidly (12 days) without scars while the wound state can be diagnosed by the change in color of the dressing patch. The multifunctional wound dressing patch developed in this study is expected to promote wound healing and monitor wound state; thus, facilitating convenient wound management. Abstract : A multifunctional wound dressing patch capable of rapid wound healing, wound protection, and wound state monitoring based on hyaluronic acid/gelatine/dexpanthenol nanofibers and curcumin/polycaprolactone microfibers are developed. In addition, the dressing's antimicrobial and pH colorimetric properties are evaluated. Furthermore, the dressing's actual healing, protection, and monitoring capabilities are evaluated through a mouse wound model.